Given f(x) = –x3 – 2x2 – x – 3, find f(–2), f(0), and f(2).?



Answers:
Assuming that the 1st term is x cubed, and the 2nd is x

squared, then

f[-2]=-[-2]^3-2[-2]^2-[-2]-3

=8-4+2-3

=3.

f[0]= 0-0-0-3

=-3

f[2]=-[2]^3-2[2]^2-2-3

=-8-4-2-3

=-17.Hope this helps, Twiggy
depends what that 2x2 is in the middle- if it is 2 times 2 then here are the answers:
f(-2)= 1
f(0)= -7
f(2)= -15
answers-
f(-2) -- 11
f(0)-- -3
f(2)-- -23

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.



More Questions & Answers...
  • What is the pH of 0.35M of HCl??
  • Today's my first day in AP Math. Pls help!?
  • Homework Physics help!!!! PLEASE?
  • Help, Essay Outline?
  • Know any good science fair projects?
  • Just 2 sentences help?
  • Please help me essay?
  • Map projections?
  • Copyright 2006-2009 EduQnA.com All Rights Reserved.